Dietary Debaryomyces hansenii promotes skin and skin mucus defensive capacities in a marine fish model - Sanahuja, Ignasi; Fernandez-Alacid, Laura; Torrecillas, Silvia; Ruiz, Alberto; Vallejos-Vidal, Eva; Firmino, Joana P.; Reyes-Lopez, Felipe E.; Tort, Lluis; Tovar-Ramirez, Dariel; Ibarz, Antoni; Gisbert, Enric (Frontiers in Immunology, 2023)
The present study explores the effects of two supplementation levels of Debaryomyces hansenii (1.1% and 2.2%) as a probiotic in a reference low fish meal-based diet on the skin mucosal tissue in Sparus aurata. This study includes the evaluation of fish performance coupled with a holistic study of the skin mucosa: i) a transcriptomic study of the skin tissue, and ii) the evaluation of its secreted mucus, both in terms of skin mucosal-associated biomarkers and its defensive capacity by means of co-culture analysis with two pathogenic bacteria. Results showed that after 70 days of diet administration, fish fed the diet supplemented with D. hansenii at 1.1% presented increased somatic growth compared to fish fed the control diet, as well as a better feed conversion ratio. In contrast, fish fed the diet including 2.2% of the probiotic presented intermediate values. Regarding gene regulation, the probiotic administration at 1.1% resulted in 712 differentially expressed genes (DEGs), among which 53.4% and 46.6% were up-and downregulated, respectively. In particular, D. hansenii modulated some skin biological processes related to immunity and metabolism. Specifically, D. hansenii administration induced a strong modulation of some immune biological-related processes (61 DEGs), mainly involved in B-and T-cell regulatory pathways. Furthermore, dietary D. hansenii promoted the skin barrier function by the upregulation of anchoring junction genes (23 DEGs), which reinforces the physical defense against potential skin damage. In contrast, the skin showed modulated genes related to extracellular exosome and membrane organization (50 DEGs). This modulated functioning is of great interest, particularly in relation to the increased skin mucus defensive capacity observed in the bacterial co-culture in vitro trials, which could be related to the increased modulation and exudation of the innate immune components from the skin cells into the mucus. In summary, the modulation of innate immune parameters coupled with increased skin barrier function and cell trafficking, potentiates the skin's 3 physical barrier and mucus defensive capacity, while maintaining the skin mucosa homeostatic immune and metabolic status. These findings confirmed the advantages of D. hansenii supplementation in low fish meal-based diets, demonstrating the probiotic benefits on cultured marine species.